Initiation and Formulation of Internationalization of Islamic Religious Higher Education - Saepudin, Didin; Asmawi, Asmawi; Sujoko, Imam; Sapiudin, Sapiudin (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
AbstractGlobalisation trends and free trade have emerged as catalysts for the internationalisation of higher education institutions. The internationalisation of PTKI has primarily been spearheaded by State Islamic University (UIN) Syarif Hidayatullah Jakarta and UIN Sunan Kalijaga Yogyakarta, particularly within their Postgraduate Programs (PPs). However, the efficacy of these initiatives necessitates critical review and evaluation, hence the imperative for this research. This qualitative, multi-case study employs internationalisation as the unit of analysis, gathering data through documentary studies and in-depth interviews. Following verification, reduction, and categorisation, the data were analysed utilising discourse and thematic techniques. This study focuses on the Postgraduate Schools (SPs) of UIN Jakarta and UIN Yogyakarta. The findings reveal that indicators of internationalisation across various dimensions, including management, teaching and educational staff, students, research, collaboration, and international reputation, have been pursued by the SPs of UIN Jakarta. However, one notable absence is the provision of international study programs at both the master’s and doctoral levels, a feature already present within the PPs of UIN Yogyakarta.AbstrakTren globalisasi dan perdagangan bebas telah menjadi salah satu pendorong bagi internasionalisasi lembaga pendidikan tinggi. Internasionalisasi Perguruan Tinggi Keagamaan Islam (PTKI) telah diinisiasi, dirancang, dan bahkan diimplementasikan oleh Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta dan UIN Sunan Kalijaga Yogyakarta, khususnya Program Pascasarjana mereka. Namun, implementasinya perlu ditinjau kembali dan dievaluasi; oleh karena itu, ini adalah urgensi dari penyelenggaraan penelitian ini. Penelitian ini adalah studi kualitatif dan multi kasus di mana internasionalisasi digunakan sebagai unit analisis yang mengarah pada pengumpulan data melalui studi dokumen dan wawancara mendalam. Setelah verifikasi, reduksi, dan kategorisasi, data dianalisis menggunakan teknik diskursus dan tematik. Objek dalam penelitian ini adalah Program Studi (PSs) UIN Jakarta dan UIN Yogyakarta. Penelitian ini menunjukkan bahwa indikator internasionalisasi lembaga pendidikan tinggi dalam Manajemen, pengajaran dan staf pendidik, mahasiswa, penelitian, kerjasama, dan reputasi internasional telah dilakukan dan terus dikejar oleh Program Pascasarjana (SPs) UIN Jakarta. Satu indikator yang absen dari SPs UIN Jakarta adalah program studi internasional baik pada tingkat magister maupun doktoral. Sebagai gantinya, program studi internasional telah ada di PPs UIN Yogyakarta.How to Cite: Saepudin, D., Asmawi, Sujoko, I., & Sapiudin. (2023). Initiation and Formulation of Internationalization of Islamic Religious Higher Education. TARBIYA: Journal of Education in Muslim Society, 10(2), 192-206. doi:10.15408/tjems.v10i2.34551.